The transposition of the Private Enforcement Directive: a critical perspective - Costeira, Maria José (UNIO – EU Law Journal, 2019)
This article analyses the proposal of transposition of the Private Enforcement Directive into the Portuguese legal system. It examines several aspects of the preliminary draft, which went through public discussion, but it highlights, specially, the articles about definitions, liability, means of proof and the potential impacts it could have on the organisation of the Portuguese judicial system. It criticises the incoherencies and points out some problematic aspects of the proposal and the necessary amendments that should be made to make the law stronger.